Melatonin treatment following stroke induction modulates l-arginine metabolism - Nair, Shiva M.; Rahman, Rosanna M. A.; Clarkson, Andrew N.; Sutherland, Brad A.; Taurin, Sebastien; Sammut, Ivan A.; Appleton, Ian (Journal of pineal research, 2011)
:  The efficacy of melatonin treatment in experimental stroke has been established. Some of the neuroprotective properties have been attributed to its anti‐oxidant and anti‐inflammatory effects. Nitric oxide synthases (NOS) and cyclooxygenases (COX) are considered to have a significant role in the inflammatory milieu occurring in acute stroke. While previous reports have shown that pretreatment with melatonin in a stroke model can modulate NOS isoforms, the effect of post‐treatment with melatonin on l‐arginine metabolism has not been investigated. This study initially examined the effect of melatonin (1 nm–1 mm) on l‐arginine metabolism pathways in human fibrosarcoma fibroblasts (HT‐1080) fibroblasts. Evidence of neuroprotection with melatonin was evaluated in rats subjected to middle cerebral artery occlusion (MCAO). Animals were treated with three daily doses of 5 mg/kg i.p., starting 1 hr after the onset of ischemia. Constitutive NOS activity but not expression was significantly increased by in vitro exposure (72 hr) to melatonin. In addition, melatonin treatment increased arginase activity by increasing arginase II expression. In vivo studies showed that melatonin treatment after MCAO significantly inhibited inducible NOS activity and attenuated expression of the inducible isoform, resulting in decreased total NOS activity and tissue nitrite levels. COX activity was significantly reduced with melatonin treatment. The neuroprotective anti‐inflammatory effects of melatonin were consistent with the substantial reduction in infarct volume throughout the cortex and striatum and recovery of mitochondrial enzyme activities. The evidence presented here suggests that modulation of l‐arginine metabolism by melatonin make it a valuable neuroprotective therapy for stroke.